Measuring the One Health impacts associated with creating access to veterinary care before and during the COVID-19 pandemic - Sloane M. Hawes; Kaleigh M. O’Reilly; Tess M. Mascitelli; Jordan Winczewski; Romi Dazzio; Amanda Arrington; Kevin N. Morris (Frontiers in Public Health)
Integrating community perceptions into One Health assessments is critical to understanding the structural barriers that create disproportionate health outcomes for community members, their pets, and the ecosystems that encompass them, particularly in historically marginalized and under-resourced communities. The validated One Health Community Assessment (OHCA) survey instrument was used to evaluate the associated impacts of The Humane Society of the United States’ Pets for Life (PFL) programming on communities’ perceptions of One Health. This evaluation took place across two phases, totaling four years. In phase one (May 2018 – December 2019), the PFL intervention was administered to one urban and one rural under-resourced community, while two demographically-paired communities served as comparison sites. Five OHCA subscales (human health, pet health, environmental health, community health, perceived links) were employed to measure changes in perceptions of One Health and fourteen OHCA items were used to measure perceptions of access to human healthcare, pet care, and the environment. Initiation of the confirmatory second phase of the study (May 2020–October 2021), in which all four communities received the intervention, coincided with the onset of the COVID-19 pandemic. The pandemic and its resulting public health mandates hindered both PFL programming and data collection. Generalized Estimating Equations were employed in both the first and second phase analyses to model changes in perceptions of One Health associated with the PFL intervention. In the study’s first phase, PFL in the urban community was associated with significant increases in perceptions of community health and environmental health, and perceived access to human health care, pet care, and the environment. The presence of PFL during the study’s second phase was associated with increased perceptions of environmental health. The variables of PFL and the pandemic were not able to be isolated within the analyses. However, due to the severe, negative One Health implications associated with the COVID-19 pandemic, the phase two results were interpreted from the perspective of the pandemic being the largest driver of the results. The results are consistent with previous research on the effects of the pandemic on community perceptions of health. These findings offer initial support for the hypothesis that deployment of resources focused on companion animals may affect perceptions across the One Health triad and confirms previous research on effects of the COVID-19 pandemic.